The “Broken Chalice”: Stasis, Sterility and Death in The Dubliners - Mukherjee, Shritama (International Journal of English Literature and Social Sciences (IJELS), 2019)
James Joyce’s The Dubliners is replete with images of stagnancy in life. Discomfort and inescapability reign large in the lives of the characters in this collection of stories. The present paper is an attempt to understand the stagnancy in life that prevailed in Ireland of the early 1900s and how Joyce vehemently responded to it. His vision of his country and countrymen included an understanding of how the dreary and corrupt motherland encroached upon the lives of men and women so much so that neither the youth was spared nor the old and the dying. Ireland, in Joyce’s eyes, was decaying and rotting in spirit and that very strain had invaded the lives of his countrymen. This paper is an examination of how Joyce probes into the moral corruption and degeneration, examining the emotional stasis that had reduced his countrymen to mere “hollowmen”.